2016
DOI: 10.1007/s12088-016-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Ability of Different Isolates of Entomopathogenic Fungi Beauveria bassiana (Balsamo) Vuillemin in Stem and Leaf Tissues of Maize (Zea mays L.)

Abstract: The present study was conducted to examine the ability of six promising indigenous isolates of Beauveria bassiana (NBAII-Bb-5a, 7, 14, 19, 23 and 45) as an endophyte in maize stem and leaf tissues. Maize seedlings (var. Nithyashree) were inoculated with conidial suspensions and were examined for endophytic establishment in leaf and stems at different intervals during 15-90 days after treatment. All six isolates showed colonization in stem and leaf tissues with varying abilities of colonization and persistence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 9 publications
4
16
0
Order By: Relevance
“…1 Effectiveness of the commercial strains Beauveria bassiana Bb-18 and Metarhizium anisopliae Ma-30 in the control of the second instar of Spodoptera frugiperda larvae host plant part and the method used. Renuka et al (2016) observed that stems of Z. mays were also colonized by B. bassiana; however, the availability and persistence on the plant tissues varied according to their age (high persistence in young tissues). Despite several authors have demonstrated that B. bassiana as endophyte of maize, others have been revealed that after the inoculation of this EPF on maize seeds, no colonization of plant tissues was obtained (Tall and Meyling 2017).…”
Section: Resultsmentioning
confidence: 99%
“…1 Effectiveness of the commercial strains Beauveria bassiana Bb-18 and Metarhizium anisopliae Ma-30 in the control of the second instar of Spodoptera frugiperda larvae host plant part and the method used. Renuka et al (2016) observed that stems of Z. mays were also colonized by B. bassiana; however, the availability and persistence on the plant tissues varied according to their age (high persistence in young tissues). Despite several authors have demonstrated that B. bassiana as endophyte of maize, others have been revealed that after the inoculation of this EPF on maize seeds, no colonization of plant tissues was obtained (Tall and Meyling 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, B. bassiana strains exhibited better tissue colonizing ability in mature/young stem and leaf tissues when they were applied as oil formulation through foliar application. In another study (Renuka et al, 2016) oil formulation spray of B. bassiana isolates exhibited better endophytic ability when compared to aqueous conidial suspension spray. This might be due to loss of viability, decreased conidial germination on leaf surfaces.…”
Section: Establishment Of Endophytic Colonization Of Beauveria Bassiamentioning
confidence: 95%
“…In our earlier studies through laboratory bioassay (Renuka et al, 2015;2016), six promising strains of B. bassiana 7,14,19,23 and 45) were identified against C. partellus and were established as endophytes in maize stem and leaf tissues by artificial inoculation through foliar sprays of conidial suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…sorghum FA [73,77] SD [77] tobacco FA [82] ST [82] RD [82] wheat FA [82,94] SD [96,97] ST [94] RD [82] soybean FA [82] corn FA [95] maize FA [74,84,98] SI [74] RD [82] ST [32] potato FA [99] coffee FA [76,100] SI [76] SD [76] tomato FA [81,101] SD [17,27,34,103] SI [104] RD [81] ST [103,104,107] grapevine FA [31,90] banana SI [108] RD [108] fava bean ST [56] common bean ST [16] SD [78] cotton ST [27,70] soybean RD [82] cassava SD [109] sweet pepper SD [57] rice FA [110] Table A1. Cont.…”
Section: Beauveria Bassianamentioning
confidence: 99%